2016
DOI: 10.3892/etm.2016.3290
|View full text |Cite
|
Sign up to set email alerts
|

Expression of hyperpolarization-activated cyclic nucleotide-gated channel isoforms in a canine model of atrial fibrillation

Abstract: Abstract. The aim of the present study was to analyze the mRNA and protein expression levels of atrial hyperpolarization-activated cyclic nucleotide-gated (HCN) channel isoforms in the left atrial muscle of dogs with multiple organ failure. A total of 14 beagle dogs with multiple organ failure, including seven cases with sinus rhythm and seven cases with atrial fibrillation (AF), underwent surgery to remove a sample of left atrial appendage tissue. The expression levels of a number of HCN channel subtypes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…[28][29][30][31] Cardiac HCN2 plays an important role in the electrical remodeling of cardiac hypertrophy and increases the risk of arrhythmia. [32][33][34][35] HCN2 is considered to be the molecular propagators of the ventricular If. 8 The If current is a mixed K + /Na + depolarizing inward current, which contributes to the depolarization of cardiac F I G U R E 4 TSH affects the expression of miR-1a and HCN2 in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[28][29][30][31] Cardiac HCN2 plays an important role in the electrical remodeling of cardiac hypertrophy and increases the risk of arrhythmia. [32][33][34][35] HCN2 is considered to be the molecular propagators of the ventricular If. 8 The If current is a mixed K + /Na + depolarizing inward current, which contributes to the depolarization of cardiac F I G U R E 4 TSH affects the expression of miR-1a and HCN2 in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed that the expression of HCN2 in cardiomyocytes under pathological conditions (such as end‐stage heart failure, hypertrophic cardiomyopathy, and acute myocardial infarction) was significantly increased 28–31 . Cardiac HCN2 plays an important role in the electrical remodeling of cardiac hypertrophy and increases the risk of arrhythmia 32–35 . HCN2 is considered to be the molecular propagators of the ventricular If 8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AF is a pathological condition in which ionic current remodeling has been demonstrated [14] . Regarding If current, an association between HCN overexpression in atrial and pulmonary vein cardiomyocytes and presence of AF has been reported in animal models and human [15][16][17][18] . In a canine model, He et al [17] demonstrated that mRNA and protein expression levels of HCN2 and HCN4 in the AF group were significantly increased when compared with the control group.…”
Section: Pacemaker Funny Current In Healthy Heart and Under Pathologimentioning
confidence: 95%
“…Regarding If current, an association between HCN overexpression in atrial and pulmonary vein cardiomyocytes and presence of AF has been reported in animal models and human [15][16][17][18] . In a canine model, He et al [17] demonstrated that mRNA and protein expression levels of HCN2 and HCN4 in the AF group were significantly increased when compared with the control group. Li et al [18] analyzed right atrial appendage samples collected from 60 patients undergoing coronary artery bypass grafting; they observed that mRNA and protein expression levels of HCN2 and HCN4 channels in the right atrial appendage increased with age.…”
Section: Pacemaker Funny Current In Healthy Heart and Under Pathologimentioning
confidence: 95%